Effect of pH on the solubility and volumetric change of ready-to-use Bio-C Repair bioceramic material - Luana Raphael da SILVA; Jader Camilo PINTO; Juliane Maria GUERREIRO-TANOMARU; Mário TANOMARU-FILHO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Acidic pH can modify the properties of repair cements. In this study, volumetric change and solubility of the ready-to-use bioceramic repair cement Bio-C Repair (BCR, Angelus, Londrina, PR, Brazil) were evaluated after immersion in phosphate-buffered saline (PBS) (pH 7.0) or butyric acid (pH 4.5). Solubility was determined by the difference in initial and final mass using polyethylene tubes measuring 4 mm high and 6.70 mm in internal diameter that were filled with BCR and immersed in 7.5 mL of PBS or butyric acid for 7 days. The volumetric change was established by using bovine dentin tubes measuring 4 mm long with an internal diameter of 1.5 mm. The dentin tubes were filled with BCR at 37°C for 24 hours. Scanning was performed with micro-computed tomography (micro-CT; SkyScan 1176, Bruker, Kontich, Belgium) with a voxel size of 8.74 µm. Then, the specimens were immersed in 1.5 mL of PBS or butyric acid at and 37 °C for 7 days. After this period, a new micro-CT scan was performed. Bio-C Repair showed greater mass loss after immersion in butyric acid when compared with immersion in PBS (p<0.05). Bio-C Repair showed volumetric loss after immersion in butyric acid and increase in volume after immersion in PBS (p<0.05). The acidic pH influenced the solubility and dimensional stability of the Bio-C Repair bioceramic cement, promoting a higher percentage of solubility and decrease in volumetric values.